Emotion-related learning in patients with social and emotional changes associated with frontal lobe damage. Issue 12 (December 1994) - Rolls, E T; Hornak, J; Wade, D; McGrath, J
Abstract : A group of patients with damage to the ventral part of the frontal lobes was severely impaired relative to a group of patients without damage in this area (the non-ventral group) in the reversal and in the extinction of simple visual discrimination tests. In these tests they continued to make responses to a previously rewarded stimulus. Patients often reported verbally that the contingencies had changed, but were unable to alter their behaviour appropriately. These impairments occurred independently of IQ or verbal memory impairments. The perseverative touching of a previously rewarded stimulus is consistent with work with non-human primates showing impaired reversal and extinction after orbitofrontal lesions. Performance on these reversal and extinction tests was highly correlated with scores obtained on a behaviour questionnaire, which reflected the degree of disinhibited and socially inappropriate behaviour exhibited by patients. It is suggested that a difficulty in modifying responses, especially when followed by negative consequences, as manifested in these simple laboratory tests, may contribute to the inappropriate behaviour shown in daily life by patients with frontal lobe damage.